Knee muscle and tendon stiffness in professional soccer players: a shear-wave elastography study - Tas, S.; Özkan, Ö.; Karaçoban, L.; Dönmez, G.; Çetin, A.; Korkusuz, F. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: It is well known that several risk factors such as fatigue, previous injury, muscle strength deficit or imbalance are related to a higher incidence of knee injuries in professional soccer players. Knee muscle and tendon stiffness may be another factor that is related to knee injuries in professional soccer players. Therefore, the aim of the present study was to investigate the differences between professional soccer players and healthy sedentary males in terms of the stiffness of patellar tendon (PT), quadriceps tendon (QT), and rectus femoris muscle (RF) and vastus medialis muscle (VM). METHODS: The study group was comprised of 17 professional male soccer players in age range of 24-37 years. The control group was comprised of 22 healthy sedentary males in an age range of 21-36 years. Shear-Wave Velocity (SWV) measurements of the selected muscles and tendons were performed using an ultrasonography device with a lineal probe. RESULTS: The professional soccer players had lower SWV of PT (P=0.024) and QT (P<0.001) in the dominant leg compared to the control group; however, SWV of PT (P=0.455) and QT (P=0.827) in the non-dominant leg were similar in both groups. SWV of RF was higher in both dominant and non-dominant legs in professional soccer players compared to the control group (P<0.05); however, SWV of VM was similar in both groups (P>0.05). CONCLUSIONS: Professional soccer players had lower PT and QT stiffness. On the other hand, they had higher RF stiffness compared to sedentary individuals. Furthermore, VM stiffness was similar in both groups.